11th annual CVMBS research day scientific proceedings - Colorado State University. College of Veterinary Medicine and Biomedical Sciences, author (Colorado State University. Libraries, 2010)
Includes the Pfizer Research Award winner and abstracts only of the oral sessions and posters.
CVMBS research day 2010
Colorado State University, College of Veterinary Medicine and Biomedical Sciences, 11th annual CVMBS research day scientific proceedings
Held in the Hilton Hotel on January 23, 2010, Fort Collins, Colorado.
Keywords: Veterinary medicine -- Congresses; Veterinary medicine -- Research -- Congresses